The main gastroenterology resort of Germany Bad Kissingen - A. M. Nogaller; V. Ya. Shvarts (Бюллетень сибирской медицины, 2012)
The information on the largest gastroenterology resort of Germany Bud Kissingen is presented. The main medical factor of a resort is external and especially internal application of mineral waters. With medical objective Bud Kissingen uses seven sources. The information on history of opening, structure of water of sources, the basic places of interest, medical means of a resort is given.